2016
DOI: 10.1007/s40094-016-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of thermal diffusivity of Au nanoparticles: effects of concentration particle size

Abstract: In this article, Au nanoparticles in polyvinylpyrrolidone (PVP) solution were prepared by gamma radiation at different concentrations. The solutions were irradiated at doses of 50 kGy for making different sizes. The average sizes of particle in the prepared samples were measured using the nanophox machine. A dual-beam mode-mismatched thermal lens (TL) method was used to investigate the effect of thermal diffusivity of samples. The TL measurement was carried out using a green diode laser (wavelength 532 nm, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Generally, the thermal effect in the samples increased when the time interval between the laser pulses was shorter than the thermal diffusion time of the sample, i.e., when , where is the beam diameter and is the thermal diffusion coefficient (where is the thermal conductivity, is the specific heat capacity, and is the density of the Au NPs). The selected femtosecond laser had a time of about 12.5 ns between the laser pulses, which was much shorter than the thermal diffusion time of the Au NPs [ 45 , 46 ]. This meant that the samples were not able to return to their equilibrium state within the time between the laser pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the thermal effect in the samples increased when the time interval between the laser pulses was shorter than the thermal diffusion time of the sample, i.e., when , where is the beam diameter and is the thermal diffusion coefficient (where is the thermal conductivity, is the specific heat capacity, and is the density of the Au NPs). The selected femtosecond laser had a time of about 12.5 ns between the laser pulses, which was much shorter than the thermal diffusion time of the Au NPs [ 45 , 46 ]. This meant that the samples were not able to return to their equilibrium state within the time between the laser pulses.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this critical issue, nanomaterials have been considered as a suitable candidate in this eld owing to their unique physical and chemical properties such as increased surface to volume ratio, high diffusivity, and excellent reactivity. 4,5 In particular, metal oxide nanoparticles (NPs) are identied as ideal candidates for degrading organic pollutants in contaminated water and effective destruction of pathogens. 6,7 Among the wide range of metal oxide NPs, titanium dioxide (TiO 2 ) is widely investigated in the elds of photocatalysis and antibacterial activity as the result of its remarkable physiochemical properties inclusive of stability and super nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Shahariari et al showed that thermal diffusivity of a material increased with concentration from greater electron-phonon relaxation and subsequent phonon scattering at the nanoparticle media interface. Larger thermal diffusivities allow for increased thermal propagation, thus implying faster changes from the dynamic driving force to the steady-state driving force [31]. Additionally, Howard et al demonstrated a plateau of thermal energy transfer from AuNPs, which allows for lower concentration AuNP-PDMS films to have a greater change in slope at a smaller concentration than for larger AuNP concentrations, matching measured results [20].…”
Section: Effects Of Aunp Concentrationmentioning
confidence: 56%